Application of HACCP in Wheat Flour Milling Process In PT. XYZ - Andini, Chairunnisa Putri (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
The implementation of HACCP (Hazard Analysis Critical Control Point) in PT. XYZ is carried out to prevent obstacles during the production process and increase consumer trust. PT. XYZ is a company engaged in the production of wheat flour to food and non-food products made from wheat. In the wheat flour production process, it goes through several important processes to produce products that meet the standards. The wheat flour production process passes through cleaning and milling which uses various types of equipment. The use of this equipment needs good monitoring and maintenance to be able to work and produce quality products that are trusted by consumers. So, to achieve this, an analysis was carried out which aims to determine the application of HACCP in the wheat flour production process in PT. XYZ. The analysis methods used were interviews, observation, and active participation in the production process in PT. XYZ. In the analysis of the application of HACCP in PT. XYZ, it was found that in the wheat flour production process there were no CCP (Critical Control Point) hazards that had a significant effect, but there were OPRP (Operational Pre Requisite Program) and PRP (Pre Requisite Program) hazards on several production machines used.